1981
DOI: 10.1159/000112738
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Forms of Acetylcholinesterase in the Developing Chick Visual System

Abstract: The developmental profiles of the enzyme acetylcholinesterase, and of some of its quaternary structural forms, characterized by discrete sedimentation coefficients, have been comparatively analyzed in chick retina and optic tectum, between embryonic day 8 and day 10 after hatching. Four molecular species of AChE have been characterized in both retina and tectum during this developmental period: two of them with sedimentation coefficients of 11S and 6S, accounting together for 94–99% of the AChE activity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The improved ex traction of the quail forms with the MgC me dium and earlier reports of improved extrac tion by cholate containing medium by Ramir ez and colleagues [1,33] illustrate the impor tance of the techniques used to solubilize and separate AChE forms.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The improved ex traction of the quail forms with the MgC me dium and earlier reports of improved extrac tion by cholate containing medium by Ramir ez and colleagues [1,33] illustrate the impor tance of the techniques used to solubilize and separate AChE forms.…”
Section: Discussionmentioning
confidence: 80%
“…It solubilized virtually 100% of the AChE ac tivity from homogenates of chicken muscle cultures and more than 85% of the AChE ac tivity of quail muscle culture homogenates. NaT buffer, commonly used for this purpose [1,26,27,33], was less effective in solubiliz ing AChE. …”
Section: Extraction O F Ac He From Culturesmentioning
confidence: 99%
“…It has been reported that AChE and BChE occur in retina (Barat et al, 1980;Villafruela et al, 1981;Layer and Sporns, 1987;Hutchins, 1987) and in RPE (Martelly and Gautron, 1988;Salceda and Martinez, 1992;. Globular AChE forms predominate in chick retina.…”
Section: Introductionmentioning
confidence: 97%
“…The molecular complexity of acetylcholinesterase (AChE: EC 3.1.1.7) in the chick retina has been extensively studied Gomez-Barriocanal et al, 1981;Villafruela et al, 1981;Barat et al, 1983). As in many other neural structures with a cholinergic component, chick retina contains both asymmetric (A-forms) and globular (G-forms) AChE isoenzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, chick retinal G-forms are mainly of the detergent-soluble type (MassouliC and Bon, 1982). These molecular species of retinal AChE show distinctive patterns of embryonic and postnatal development (Villafruela et al, 1981;Barat et al, 1983).…”
Section: Introductionmentioning
confidence: 99%